Optimal location queries on road network - Vu, Minh Tam (2011)
Optimal location queries are queries dealing with locations in spatial databases that best satisfy a cost metrics. Optimal location queries can be applied in various practical scenarios such as locating a restaurant or retail store to maximize the inflow of customers. There have been works addressing optimal location problems, which solve the queries in Lp spaces. However, Lp space datasets which assume free movements between points do not accurately reflect actual road networks in which connectivity restricts the movement. Therefore, it is necessary for a solution framework to account for the underlying connections in the road network.The aim of this project is to implement and evaluate the efficiency of one pioneer solution framework in solving optimal location queries in road network databases, and also to give the algorithm a graphical interface. Solutions to two variants of optimal location queries, Competitive Location and Min Sum Location, are discussed in this report. Competitive Location queries are concerned with looking for locations that attract a largest weighted sum of clients while Min Sum Location queries with locations that help minimize the average distance between a client and its nearest facility.